A qualitative review of approaches of information technology in banking sector in China: a literature analyses. (1st January 2013) - Naem, Meraj; Abu Faiz, Mohammad; Kabiraj, Sajal
This paper is aimed to critically appraise extensions, and replications of technology acceptance model (TAM) in context of internet banking in China. The paper also presents the limitation and adaptability of reviewed models across different cultures. The paper examines 20 different extensions made to TAM in context of internet banking reported in the literature. The study provides knowledge base for bank management to understand the individual predictors of internet banking, particularly in case of developing countries like China. Furthermore study showed that risk, trust, efficacy, social influence are important simulators of cognitive beliefs. It is considered that the current development of the knowledge base on internet banking adoption models (TAM) should lead to analysis of key dimensions, which have significant impact on behaviour, across various countries and cultures, especially in China.